A study on the implementation of design elements for children colouring books / Nurul Fathiah Nathasha Thaib - Thaib, Nurul Fathiah Nathasha (2013)
The purpose of this research is to study on the implementation of design elements for children coloring books . Teach key concepts in art and design through an engaging coloring book and jump-starts the creative process while introducing fundamental art vocabulary and ideas. Open spaces encourage children or students to explore their own artistic sensibilities. Concepts covered include the elements of design, composition, drawing and coloring techniques. Coloring book programs are often simple and they can develop anything from there just click some skills. The only task is to fill-in predefined regions by a selected color. This research exploits the possibilities offered by a book to do more.Based on discussions with a clinical psychologist, we designed an interactive coloring book concept to help preschool children in development of creative and logical thinking and basic book operation skills. Children are offered a simple page for coloring where individual objects can interact with their own input. The objects behave exactly as the children know from their every day life. The object reaction is physically simulated. The book can be designed using elementary objects, images, sticker, and logic.